Propuesta de proceso para el servicio de delivery post covid-19 del establecimiento “Hornados Rosita” de la ciudad de Ibarra - Antamba Cadena, Lander Santiago (2022)
This research deals with the creation of the delivery service of the establishment called Hornados Rosita. This family place is located in the urban area of the city of Ibarra in Ecuador\; The objective of this work is to propose the implementation of a Post COVID-19 delivery service to facilitate the acquisition of a safe product by the consumer. The methodology used defends a work with applied inquiry with a qualitative approach which adopts exploratory and explanatory research by surveying clients of the aforementioned establishment, as well as interviews with teachers and gastronomic experts, in order to obtain the necessary information for the post-COVID delivery process. 19. It is appropriate to mention that the most notable results established a correct interest in the delivery service of the Hornados Rosita establishment, whose logistics allow the implementation of a service that in this way guarantees the quality of the product in its different aspects such as health, flavor and agility in each one of the processes thus reaching the satisfaction of each and every one of its customers. Implementing the aforementioned has been crucial for all establishments and even more relevant for those dedicated to the sale of food and beverages who saw the need to reformulate their processes and thus prevent the spread of the coronavirus. It is concluded that the emergence of the pandemic caused by COVID-19 impacted all types of companies, the same ones that had to adapt to the needs of the moment and innovate.